Analisis Pengelolaan Keuangan Keluarga dan Literasi Keuangan Wanita di Dusun 20 Desa Klambir Lima Kebun - Handriyani Dwilita; Pipit Buana Sari (CERED Indonesia Institute, 2020)
This study aims to provide an overview of the proxied factors to describe the condition of women's financial literacy in terms of understanding financial management. The number of respondents was 56 people. This study uses canonical correlation analysis techniques. The results of the study reveal that from the three testing models, the third model shows a positive relationship between the independent variables, namely Financial Budget, Family Financial Reporting and Tabungan Behavior with the dependent variable, namely Financial Skills and Financial Behavior.